Penghambatan Fusarium oxysporum oleh Kultur Filtrat Bakteri Endofit dari Tanaman Kedelai secara in Vitro - Novi Malinda; Bonny Poernomo Wahyu Soekarno; Titiek Siti Yuliani (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Seed borne pathogen play an important role as source of inoculum for disease incidence in the field and it becomes a major constraint in certified seed production. Research was conducted to isolate potential endophytic bacteria from soybean plants and evaluate its culture filtrate for inhibition effect of seedborne fungi on soybean seed, i.e. Fusarium oxysporum. The result showed that out of forty eight endophytic bacteria isolates that were nonpathogenic, there were three potential isolates that can inhibit the growth of F. oxysporum, i.e. EDA 3, EBA 6, and EBA 7 with percent inhibition of 60.14%, 57.69%, and 57.08%, respectively. The filtrate culture of EBA 7 showed the highest inhibition (34.88%) by in vitro test. Therefore, those three isolates of endophytic bacteria might be used as biocontrol agent to inhibit the growth of F. oxysporum.